2006
DOI: 10.1111/j.1468-1293.2006.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of rash associated with efavirenz in HIV‐infected patients with preceding nevirapine‐associated rash

Abstract: ObjectiveTo determine the incidence and risk factors of rash associated with efavirenz in HIV-infected patients with preceding nevirapine-associated rash. MethodsA retrospective cohort study was conducted in HIV-infected patients diagnosed with nevirapineassociated rash who subsequently received efavirenz between July 2003 and January 2005. Patients were followed up for 3 months after receiving efavirenz. Possible risk factors, including demographics, previous opportunistic infections, CD4 cell count, viral lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 20 publications
2
28
1
Order By: Relevance
“…[11][12][13] Kiertiburanakul et al found that history of drug allergy and CD4 cell count < 100 cells/µl at the time of NVP initiation were predictive factors for unsuccessful switching from NVP to EFV in HIV-infected patients with preceding NVP-associated skin rash. 12 SJS often demands prolonged hospitalisation with reported length of hospitalisation ranging from 2 to 49 days.…”
Section: Discussionmentioning
confidence: 97%
“…[11][12][13] Kiertiburanakul et al found that history of drug allergy and CD4 cell count < 100 cells/µl at the time of NVP initiation were predictive factors for unsuccessful switching from NVP to EFV in HIV-infected patients with preceding NVP-associated skin rash. 12 SJS often demands prolonged hospitalisation with reported length of hospitalisation ranging from 2 to 49 days.…”
Section: Discussionmentioning
confidence: 97%
“…Wit et al 28 , reporting the results of the ATHENA Cohort Study in 2008 suggested that the majority (>90%) of HIV infected patients with CD4 counts >200 cells/L who had preceding NVP-associated rash could tolerate EFV well, suggesting that use of EFV is safe in these cases. In their study from Thailand in 2006, Manosuthi et al 20 also observed that only 8.2% developed rash associated with EFV following history of rash with NVP and a conclusion was drawn that HIV-infected patients with CD4 counts of >200 cells/mL who had preceding NVP-associated rash could tolerate EFV well.…”
Section: Discussionmentioning
confidence: 99%
“…19 Similarly, in a study conducted on Thai patients in 2006, by Manosuthi et al, only 10 (8.2%) of 122 patients who had NVP rash developed rash from EFV, leading to its discontinuation. 20 Clinical safety data regarding use of NVP in HIV-infected patients with preceding EFV associated rash are still quite limited, 13,21 whereas, switching from NVP to EFV in cases of skin rash or hepatotoxicity have seemed safer and effective. Accordingly, most clinicians are unwilling to challenge patients with NVP once rashes have been documented with EFV as both are from the same class of NNRTI and higher incidence of severe rashes associated with NVP makes such switch unsafe.…”
Section: Introductionmentioning
confidence: 99%
“…Switching from nevirapine to efavirenz and vice versa following cutaneous hypersensitivity was associated with a recurrence of severe rash although the evidence for this comes from small retrospective cases [129][130][131]. Cross-reactivity is reported to be higher between nevirapine and delavirdine which have a similar structure, but delavirdine is no longer used for the treatment of HIV disease due to its toxicity profile [132].…”
Section: Cross Reactivitymentioning
confidence: 99%